Between Silver and Guano : Commercial Policy and the State in Postindependence Peru - Gootenberg, Paul, 1954- (Book collections on Project MUSE., 2014)
This study of Peru's transformation from a tottering colonial economy based on extraction of precious bullion to a massive exporter of bulk goods like guano shows how a struggle between protectionists and free traders shaped the state. ""This is an elegant and sophisticated book that can be read on many levels, written by an author who never takes the facile road. [Its] significance is great--not just for Peruvian history but for theoretical questions relating to dependency and economic history in nineteenth-century Latin America ... Gootenberg has added a major new element to the d